Developing Culture Based English E-media to Support the Implementation of Curriculum 2013 for the Second Semester of Grade VII of Junior High Schools in Buleleng - ., Kadek Yuda Widnyana; ., Made Hery Santoso, S.Pd, M.Pd.; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This design and development research aimed at designing and developing a culture-based English e-media to support the implementation of curriculum 2013 for the second semester of grade VII of junior high schools in Buleleng sub-district. this research focused on developing e-media that is integrated with Balinese culture. The object of this reseacrh was culture-based English e-media that was developed by using Adobe Flash CS6 program. The source of data was taken from the need analysis conducted by Dewi and Batan (2015), related literatures on developing the e-media, and the result of expert judgement. The data were analyzed using qualitative and quantitative method. This research was designed based on the adaptation of Peffers et al.’s model (2007) consisted of six phases namely: (1) identifying the problem, (2) describing the objective, (3) designing and developing the product, (4) testing the product by using expert judgement, (5) evaluating the testing result, and (6) communicating the testing result. The result of experts’ judgement score showed that the total mean score was 3.8 which meaning that e-media had a good quality to be implemented in teaching and learning English for the second semester of grade VII of junior high schools in Buleleng.keyword : E-media, Culture-based, Balinese culture